Study protocol for a randomized controlled trial comparing pulse pressure variation (PPV) and central venous pressure (CVP) guidance for fluid responsiveness assessment in neurosurgical patients undergoing posterior fossa tumor resection in park bench position - Pathomporn Pin on; Srisuluk Kacha; Ananchanok Saringkarinkul; Nakan Thanakititham (PLoS ONE, 2025)
Introduction Suboccipital craniotomy in the park bench position is linked to considerable physiological alterations. Effective fluid management in this context is a challenge to anesthesiologists. No published data exist on pulse pressure variation and central venous pressure guidance in patients undergoing tumor resection in the park bench posture. We undertake a study to evaluate the concept that two approaches of goal-directed fluid treatment enhance optimal fluid management and improve hemodynamic stability. We established the fluid management protocol for this process. Methods and analysis This is a prospective randomized double-blinded study of adult patients undergoing suboccipital craniotomy to remove tumors in the park bench position. The comparison of pulse pressure variation and central venous pressure for fluid management regarding mean intraoperative fluid administration as the primary outcome. A sample size of 54 will yield over 80% power to identify a mean fluid difference of at least 500 ml between two specified methods. The secondary outcomes are data pertinent to fluid administered during and after surgery, including the lowest systolic blood pressure, serum lactate levels, vasopressor utilization, and duration of ICU stay. The statistical analysis will be validated based on the data distribution and types of data. This is the first study to examine two goal-directed fluid therapies, pulse pressure variation and central venous pressure, in patients with posterior fossa tumors and undergoing surgery in the park bench position. Researchers want to contribute novel information to the domain of fluid optimization in neurosurgery. Trial registration ClinicalTrials.gov NCT06595667.